Survey-Based Descriptive Study on University Students’ Adoption and Behavioral Patterns of IoT-Based Payment Systems in Malaysia - Sun Tong; Zhang Jia Yi; Duan XinYi; Liu Cheng Ming; Xia Xuanze; Gutianyu Gutianyu; Aliana Shazma Amir; Evawaynie Valquis Md. Isa (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2025)
This study investigates university students’ adoption, usage patterns, and behavioral perceptions of IoT-based payment systems in Malaysia. Using a survey approach, ten students were examined to explore the frequency of usage, perceived financial control, impulsivity, trust, and influence on financial decision-making. Findings reveal high adoption and habitual usage, with students exhibiting moderate trust in system security and varied perceptions of financial control. While access to digital transaction data enhances awareness, it does not necessarily translate into disciplined financial behavior, indicating a gap between insight and action. Concerns such as security, micro-spending, and app limitations were identified. The study highlights the interplay between trust, habitual use, and digital financial literacy, suggesting the need for apps to evolve from passive trackers to behavioral nudges supporting budgeting, savings, and financial decision-making. The results provide insights for developers, educators, and policymakers aiming to optimize digital financial tools for young adults.free spins no deposit ukdhltotomahjong ways